EFL STUDENTS’ SCHWA (/?/) PRONUNCIATION ERRORS IN PHONETICS AND PHONOLOGY LEARNING - Ade Putri Ifanny; Yuli Herman; Risza Dwiputri; Afdaleni Afdaleni (ELP (Journal of English Language Pedagogy), 2026)
The schwa vowel (/?/) is the most frequently occurring vowel in English and plays an important role in natural speech. Although previous studies have examined schwa pronunciation among Indonesian EFL learners, few have analyzed errors based on word position and error type, particularly among students who have studied phonetics and phonology. This study aimed to analyze students’ schwa pronunciation errors according to word position and error category. A descriptive quantitative design was employed involving 15 fourth-semester students of the English Education Department at Universitas Mahaputra Muhammad Yamin, Solok. Using total sampling, data were collected through a pronunciation test consisting of 30 English words containing schwa sounds in initial, medial, and final positions. The data were analyzed using error analysis procedures. The results showed that pronunciation errors occurred in all word positions, with the highest error rate in medial-position schwa (37%), followed by final-position (29%) and initial-position schwa (13%). Substitution was the most frequent error type (25%), while omission errors were rare (2%) and no addition errors were found. These findings indicate that students’ pronunciation difficulties were mainly influenced by first-language interference, limited phonological awareness, and inadequate understanding of English stress patterns. Further studies with larger and more diverse samples are recommended.